An innovative integrated framework towards effective collaboration environments in construction. (1st January 2010) - Erdogan, Bilge; Anumba, Chimay J.; Bouchlaghem, Dino; Nielsen, Yasemin
The research reported in this paper was aimed at exploring the introduction of IT enabled collaboration environments to construction organisations and managing the changes required to obtain full benefits. The paper firstly presents the results of a literature review on the factors affecting the success of collaboration environment implementations. Secondly, it summarises the results of case studies providing the perspectives of the construction organisations on the implementation of collaboration environments. It then presents the implementation of collaboration environments and management of organisational changes (ICEMOCHA) framework developed to enable the planning and implementation of collaboration environments on construction projects whilst carrying out the organisational changes in each organisation. The paper also provides the evaluation results of the ICEMOCHA framework.